2022
DOI: 10.1073/pnas.2206708119
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of mitochondria–sarcoplasmic reticulum microdomain connectomics contributes to sinus node dysfunction in heart failure

Abstract: The sinoatrial node (SAN), the leading pacemaker region, generates electrical impulses that propagate throughout the heart. SAN dysfunction with bradyarrhythmia is well documented in heart failure (HF). However, the underlying mechanisms are not completely understood. Mitochondria are critical to cellular processes that determine the life or death of the cell. The release of Ca 2+ from the ryanodine receptors 2 (RyR2) on the sarcoplasmic reticulum (SR) at mitochondria–SR microdomains se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 51 publications
(72 reference statements)
0
3
0
1
Order By: Relevance
“… 247 Mitofusin 2, a protein essential for MERC formation, 92 is reduced in HF in mice. 248 MERCs are composed of several proteins involved in the regulation of Ca 2+ homeostasis: GRP75 (glucose-regulated protein 75), a chaperone protein, acts as a crucial linker between the IP3Rs (inositol trisphosphate receptors) on the ER and the voltage-dependent anion channel (VDAC) 1 on the outer mitochondrial membrane. 234 , 235 In vitro studies have shown that IP3R3 is responsible for Orai-mediated Ca 2+ entry and store-operated Ca 2+ entry through the formation of a complex with STIM1 (stromal interaction molecule 1) following an inositol trisphosphate signaling cascade in low Ca 2+ conditions.…”
Section: Disrupted Calcium Homeostasis and Ros Production In Hfmentioning
confidence: 99%
“… 247 Mitofusin 2, a protein essential for MERC formation, 92 is reduced in HF in mice. 248 MERCs are composed of several proteins involved in the regulation of Ca 2+ homeostasis: GRP75 (glucose-regulated protein 75), a chaperone protein, acts as a crucial linker between the IP3Rs (inositol trisphosphate receptors) on the ER and the voltage-dependent anion channel (VDAC) 1 on the outer mitochondrial membrane. 234 , 235 In vitro studies have shown that IP3R3 is responsible for Orai-mediated Ca 2+ entry and store-operated Ca 2+ entry through the formation of a complex with STIM1 (stromal interaction molecule 1) following an inositol trisphosphate signaling cascade in low Ca 2+ conditions.…”
Section: Disrupted Calcium Homeostasis and Ros Production In Hfmentioning
confidence: 99%
“…The structural connection between the mitochondria and the ER is known as the mitochondria-associated ER membrane (MAM) [ 9 ]. Disruption of the MAM structure is a significant factor in the development of HF [ 10 ]. Single-cell transcriptional profiling demonstrates MAM-related proteins preferentially accumulate in cardiomyocytes during the initial stages of cardiac hypertrophy but gradually decrease as the disease progresses [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…La causa más común de esta patología es una lesión cerebral, provocada por el aumento de la presión intracraneal o hipoxia Teri M (2019). En los pacientes de la tercera edad que presentan esta patología pueden padecer algún tipo de cardiopatía Ren L et al (2022). Es una estructura fibrótica única, alargada, tridimensional ubicada en la unión de la región intercava de la vena cava superior que bordea la cresta terminal, se origina en el marcapasos intraganglionares y se conduce a las aurículas a través de una o más vías de conducción sino auricular discretas Kalyanasundaram et al (2023).…”
Section: Introductionunclassified